A cross-sectional study to assess the out-of-pocket expenditure of families on the health care of children younger than 5 years in a rural area. Issue 3 (1st September 2018) - Shrivastava, Saurabh RamBihariLal; Shrivastava, Prateek Saurabh
Abstract : Objective: This study aimed to estimate the out-of-pocket expenditure of families on the health care of children younger than 5 years in a rural area of Kancheepuram district. Methods: A cross-sectional descriptive study was performed in a rural area of Kancheepuram district for 5 months. All households with at least one child younger than 5 years were eligible for the study, and 153 households were selected for the final study. A semistructured and pretested schedule was used to obtain information about various study variables during home visits. Ethics approval was obtained before the start of the study. Data were entered into Microsoft Excel, and statistical analysis was done with IBM SPSS Statistics version 23. Frequency distributions were calculated for all the variables. Results: The findings indicate that most children younger than 5 years were males (62.7%). The maximum out-of-pocket expenditure was for accidents/trauma and in cases of fever/malaria. Further, 96 households (53.1%) preferred private-sector health care for their ailments. Conclusion: The findings indicate that 93 of the children younger than 5 years (60.8%) had experienced one episode of illness in the previous 3 months. Further, the maximum out-of-pocket expenditure was for accident/trauma cases, and overall the largest share was for buying medications for the treatment. Significance statement: In India, a developing nation with a weak public health care delivery system, most of the general population seeks health care from the private sector. Even though the private sector neutralizes most of the deficiencies of the public sector, it accounts for a major financial burden on individuals, families, and the community through enormous health care expenditure. This study aimed to identify the out-of-pocket expenditure of families on the health care of children younger than 5 years in a rural area of Kancheepuram district, which will help policy makers to identify the prevailing trends, and thus provide them with the evidence to strengthen the response of the public health sector in the rural area.